A re-examination of the relation between democracy and international trade: The case of Africa - Christopher Balding (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Scholars and policy makers believe that democracy will bring prosperity through integration into the global economy via increased international trade. This study tests two theories as to why democracies might trade more. First, political freedom may be correlated with economic freedom, thus prompting higher levels of economic activity, thereby driving states to trade more. Second, democracy implies higher quality governance either through institutions or policy-making procedures. I utilize a bilateral gravity trade model covering approximately 150 countries from 1950 to 1999, with fixed effects for time, importers and exporters. I find the theory that democracy, and many of its components, promotes international trade unconvincing. Economic freedom does not have the expected impact on international trade levels, but quality of governance variables have broad economic and statistical significance.
Keywords: F1; O17; P16; 330; trade; democracy; governance; Africa; gravity model; Außenhandel; Demokratie; Governance-Ansatz; Gravitationsmodell; Afrika